AN EMG STUDY ON FUNCTIONAL ASPECTS OF MUSCLES MANDIBLE DYNAMICS - Cornelia Brezulianu; Maria-Antonela Beldiman; Nicoleta Ioanid; Georgiana Macovei; Elena Luca (Romanian Society of Oral Rehabilitation, 2018)
Aim of the study The aim of this study was to evaluate the muscular forces from the masseter muscles through a series of EMG records. Muscle activity was evaluated in various occlusal relationships/positions to determine possible correlations in the diagnosis and treatment of stomach system disorders. Material and methods The study was conducted on a group of 15 patients presenting clinical signs or symptoms of the dysfunctional syndrome of the dental system and with the acquisition of EMG surface signals was used a special system with 2 EMG acquisition modules in parallel. Results The results obtained from the recordings of various symmetric indices and muscle activity were assessed - equally approximate values were obtained when the apparent asymmetries were recorded in the maximum interference, and lateral movement was performed by the more active masseter muscle. Conclusions The value of the EMG examination as a paraclinical investigation is reflected in the diagnosis and treatment of dysfunctions and even in knowing how it works but needs the interpretation and development of a much wider database.